Peningkatan keterampilan menulis pantun melalui penggunaan model pembelajaran concept sentence pada peserta didik kelas V sekolah dasar - Sari, Yunita; Atmojo, Idam Ragil Widianto; Karsono, Karsono (Universitas Sebelas Maret, 2020)
The purpose of this reseacrch was to improve pantun writing skills through the use of the Concept Sentence learning model. This research is a Class Action Research which was carried out for 2 cycles, with 4 stages namely planning, implementing, acting, observing and reflecting. The research subjects were grade V students of the State Elementary School in Surakarta consisting of 14 students. Data collection techniques using observation interviews, documentation and test. The data analysis technique uses an interactive analysis model from Miles-Huberman. The results showed an increase in the first cycle obtained a percentage of 52% and in the second cycle to 92,3%. Based on the results of this research it can be concluded that the pantun writing skills increase after the application of the Concept Sentence learning model.